Market Information and Signaling in Central Bank Operations, or, How Often Should a Central Bank Intervene? - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
A central bank must decide on the frequency with which it will conduct open market operations and the variability in short-term money market that it will allow. It is shown how the optimal operating procedure balances the value of attaining an immediate target and broadcasting the central bank's intentions against the informational advantages to the central bank of allowing the free play of market forces to reveal more of the information available to market participants.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet